Preformed donor-specific HLA antibodies in living and deceased donor transplantation: a multicenter study - Ziemann, Malte; Süsal, Caner (Clinical journal of the American Society of Nephrology, 2019)
Background and objectives: The prognostic value of preformed donor-specific HLA antibodies (DSA), which are only detectable by sensitive methods, remains controversial for kidney transplantation. Design, setting, participants, & measurements: The outcome of 4233 consecutive kidney transplants performed between 2012 and 2015 in 18 German transplant centers was evaluated. Most centers used a stepwise pretransplant antibody screening with bead array tests and differentiation of positive samples by single antigen assays. Using these screening results, DSA against HLA-A, -B, -C, -DRB1 and -DQB1 were determined. Data on clinical outcome and possible covariates were collected retrospectively. Results: Pretransplant DSA were associated with lower overall graft survival, with a hazard ratio of 2.53 for living donation (95% confidence interval [95% CI], 1.49 to 4.29; P<0.001) and 1.59 for deceased donation (95% CI, 1.21 to 2.11; P=0.001). ABO-incompatible transplantation was associated with worse graft survival (hazard ratio, 2.09; 95% CI, 1.33 to 3.27; P=0.001) independent from DSA. There was no difference between DSA against class 1, class 2, or both. Stratification into DSA <3000 medium fluorescence intensity (MFI) and DSA ≥3000 MFI resulted in overlapping survival curves. Therefore, separate analyses were performed for 3-month and long-term graft survival. Although DSA <3000 MFI tended to be associated with both lower 3-month and long-term transplant survival in deceased donation, DSA ≥3000 MFI were only associated with worse long-term transplant survival in deceased donation. In living donation, only strong DSA were associated with reduced graft survival in the first 3 months, but both weak and strong DSA were associated with reduced long-term graft survival. A higher incidence of antibody-mediated rejection within 6 months was only associated with DSA ≥3000 MFI. Conclusions: Preformed DSA were associated with an increased risk for graft loss in kidney transplantation, which was greater in living than in deceased donation. Even weak DSA <3000 MFI were associated with worse graft survival. This association was stronger in living than deceased donation.